Analysis of Satisfaction to The User of The Elementery Teacher Study Program Graduates Faculty of Teacher Training and Education, Pakuan University - Novita, Lina (Journal of Humanities and Social Studies, 2017)
This research uses qualitative approach. The problem in this research is that students of PGSD graduates still have to deepen their mastery of English, lack of implementing the use of technology and information tools, and lack of expertise in self-development field. User satisfaction of graduates can be measured from 7 (seven) aspects of the ability of PGSD graduate in the field. The seven aspects are integrity (ethics and morals), professionalism (expertise by field), English, information technology skills, communication, teamwork, and self-development. User satisfaction graduates produce good values in six aspects (85.7%), namely aspects of integrity, professionalism, communication, use of information technology, teamwork, and self-development. While as much as one aspect (14.3%) the results are quite good. This aspect is English proficiency. This indicates that the study program must be really serious in improving the English language skills of PGSD students to be able to learn it better. Good listening, writing, speaking, and grammar skills. Keywords: satisfaction, users, students